Type of strabismus and changes to fusion measures - Lança, Carla (2015)
Assessing the range of vergence provides information about the patient’s ability to maintain the binocular vision. Disparity vergence measurements should be used to quantify control of an underlying eye misalignment. In the presence of a manifest deviation the testing is performed by first compensating the angle of deviation to determine prognosis. Type of deviation: a) in an exophoria there is an increase in the fast fusional convergence while in an esophoric deviation there is an increase in reflex fusional divergence to attain binocular single vision; b) convergence fusion amplitudes have been found to correlate with control of the exodeviation; c) there is a greater BO range for esos and greater BI range for exos.